Security awareness for dummies - Winkler, Ira (--For dummies., 2022)
Every organization needs a strong security program. One recent study estimated that a hacker attack occurs somewhere every 37 seconds. Since security programs are only as effective as a team's willingness to follow their rules and protocols, it's increasingly necessary to have not just a widely accessible gold standard of security, but also a practical plan for rolling it out and getting others on board with following it. Security Awareness For Dummies gives you the blueprint for implementing this sort of holistic and hyper-secure program in your organization. Written by one of the world's most influential security professionals-and an Information Systems Security Association Hall of Famer-this pragmatic and easy-to-follow book provides a framework for creating new and highly effective awareness programs from scratch, as well as steps to take to improve on existing ones. It also covers how to measure and evaluate the success of your program and highlight its value to management. - Customize and create your own program - Make employees aware of the importance of security - Develop metrics for success - Follow industry-specific sample programs.